The Impact of Teaching Entrepreneurship Engagement on Teacher’s English Proficiency, Teaching Skills, Self-Regulations and Supply Chain for Indonesian EFL Students - Saraka, Saraka (International Journal of Supply Chain Management, 2020)
Abstract- The foremost aim related to this research is to examine the impact of entrepreneurship engagement on the teachers’ English proficiency, skills and self-regulation in Indonesian English as foreign language (EFL) students. The secondary aim associated with this study is to examine the mediating role of the supply chain on the links of entrepreneurship engagement and teachers’ English proficiency, entrepreneurship engagement and teacher’s skills, and entrepreneurship engagement and self-regulation. The data were collected from the EFL students of Indonesia and analysis was performed by using the PLS-SEM. The findings indicated that positive links among the entrepreneurship engagement and teachers’ English proficiency, skills, and self-regulation. The results also indicated that the supply chain positively mediates among the nexus of entrepreneurship engagement and teachers’ English proficiency, entrepreneurship engagement and teachers’ skills, and entrepreneurship engagement and self-regulation. This literature gives the awareness to the policymakers that they should emphases on the entrepreneurship engagement that enhance the teachers’ English proficiency, skills and self-regulation.